Prolonged exposure to insulin might cause epigenetic alteration leading to insulin resistance - Shehnaz Bano; Shyam More; Dattatray S. Mongad; Abdul Khalique; Dhiraj P. Dhotre; Manoj K. Bhat; Vasudevan Seshadri (FEBS Open Bio)
Glucose homeostasis is maintained by insulin. Insulin resistance is caused by multiple factors including hereditary factors and diet. The molecular mechanism underlying insulin resistance (IR) is not completely understood. Hyperinsulinemia often precedes insulin resistance and Type 2 diabetes. We had previously shown that prolonged exposure of insulin‐responsive cells to insulin in the absence of high levels of glucose led to insulin resistance. In the present study, we show that the underlying cause for the impaired insulin signalling is the defective PI3K/AKT pathway. The observed insulin resistance is likely due to epigenetic alterations, as it can be maintained for several generations even when insulin is not provided, and epigenetic modifiers can reverse it. We also show that liver cell line (BRL‐3A) developed impaired insulin signalling upon prolonged exposure to insulin in the absence of high levels of glucose. Transcriptomic analysis of the insulin‐sensitive and resistance cells uncover altered signalling networks involved in chromatin remodelling, Rho GTPases, and ubiquitination. Furthermore, trimethylation of histone H3 at lysine 4 (H3K4me3) is increased in insulin‐resistant cells. We extended these studies to mice, and show that mice injected with low doses of insulin when fasting develop insulin resistance with impaired glucose tolerance and increased HOMA‐IR index. Altogether, these findings suggest that dysregulated synthesis of insulin in the absence of glucose stimulus could lead to epigenetic alterations that may ultimately result in insulin resistance.